TsAmE said:Let A and B be invertible n x n matrices.
Show that \(\displaystyle \mathbf{AB}\) is invertible, with \(\displaystyle \mathbf{(AB)^{-1}} = \mathbf{B^{-1}A^{-1}}\)
I am clueless with this question and dont know where to start.
TsAmE said:Pre multiplying with AB:
\(\displaystyle \mathbf{(AB)(AB)^{-1}} = \mathbf{(AB)B^{-1}A^{-1}}\)
\(\displaystyle 1 = \mathbf{(AB)B^{-1}A^{-1}}\)
Post multiplying with AB:
\(\displaystyle \mathbf{(AB)^{-1}(AB)} = \mathbf{ B^{-1}A^{-1}(AB)}\)
\(\displaystyle 1 = \mathbf{B^{-1}A^{-1}(AB) }\)
Is this right? What next are you suppose to do?